PENGARUH PERMAINAN AMPLOP AKHLAK TERHADAP PERILAKU MORAL ANAK USIA 5-6 TAHUN DI TK AL-IZHAR SCHOOL PEKANBARU - Desi Haryanti; Zulkifli N '; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:This research aim to knowthe influence envelope character game to behavior morals of 5-6 years old children at Al-Izhar School kindergarten Pekanbaru. Population of this reseacrh was Al-Izhar School kindergarten child’s, sample of researchare 17 childs. Method of research was experiment which this research tries to look for this research aim to know the influence envelope character game to behavior morals of 5-6 years old children at Al-Izhar School kindergarten Pekanbaru. Instrumental of this research used observation sheet.The result of this research that acquired available the influence envelope character game to behavior morals of 5-6 years old children at Al-Izhar School kindergarten Pekanbaru. It can be known from The results of this study have percentages obtained pretest 45,91% and posttest 80,71%, then the influence envelope character game to behavior morals of 5-6 years old children at Al-Izhar School kindergarten Pekanbaru. is80,71% - 45,91% = 34.8% . The influence envelope character game to behavior morals of 5-6 years old children at al-izhar school kindergarten pekanbaru. That is equal to 34.8% : 45,91 =75,8%Key Words: Envelope Character Game, Behavior Morals